2.13 Recent Developments in Reversible Deactivation Radical Polymerization - Yamago,S.; Lu,Y. (Free Radicals: Fundamentals and Applications in Organic Synthesis 2, 2021)
Recent developments in reversible deactivation radical polymerization, which is also called controlled or living radical polymerization, are summarized in this chapter. In particular, this chapter focuses on (1) broadening the range of applicable monomers from conjugated monomers to unconjugated monomers, (2) the expansion of the polymer structure from linear polymers to highly branched polymers, and (3) the use of light, in particular low-intensity and inexpensive visible light, to enable a higher degree of polymerization control under environmentally benign polymerization conditions.
Keywords: Referencework; Science of Synthesis; reversible deactivation radical polymerization; living radical polymerization; unconjugated monomers; highly branched polymers; hyperbranched polymers; photoactivation; photoredox catalysts